An Improved Square-always Exponentiation Resistant to Side-channel Attacks on RSA Implementation. Issue 3 (2nd July 2016) - Choi, Yongje; Choi, Dooho; Lee, Hoonjae; Ha, Jaecheol
Abstract: Many cryptographic algorithms embedded in security devices have been used to strengthen home- land defense capability and protect critical information from cyber attacks. The RSA cryptosystem with the naive implementation of an exponentiation may reveal a secret key by two types of side-channel attacks, namely passive leakage information analysis and active fault injection attacks. Recently, a square-always exponentiation algorithm in which the multiplication is traded for squarings has been proposed. This novel algorithm for RSA implementation is faster than other regularity-based countermeasures and is resistant to SPA (simple power analysis) and fault injection attacks. This paper shows that the right-to-left version of square-always exponentiation algorithm is vulnerable to several side-channel attacks, namely collision distance-based doubling, chosen-message CPA (collision power analysis), and horizontal CPA-based combined attacks. Furthermore, an improved right-to-left square-always algorithm adopting the additive message blinding method and the intermediate message update technique is proposed to defeat previous and proposed side-channel attacks. The proposed exponentiation algorithm can be employed for secure CRT-RSA (RSA based on the Chinese remainder theorem) implementation resistant to the Bellcore attack. The paper presents some experimental results for the proposed power analysis attacks using an evaluation board.